Evaluation of natural gum-based cryogels for soft tissue engineering - Bektas, Ezgi Irem; Pekozer, Gorke Gurel; Kok, Fatma Nese; Kose, Gamze Torun (Elsevier BV, 2021)
In this study, three natural biomaterials, Locust bean gum (LBG), Xanthan gum (XG), and Mastic gum (MG), were combined to form cryogel scaffolds. Thermal and chemical characterizations revealed the successful blend formation from LBG-XG (LX) and LBG-XG-MG (LXM) polymers. All blends resulted in macro-porous scaffolds with interconnected pore structures under the size of 400 μm. The swollen cryogels had similar mechanical properties compared with other polysaccharide-based cryogels. The mean tensile and compressive modulus values of the wet cryogels were in the range of 3.5-11.6 kPa and 82-398 kPa, respectively. The sustained release of the small molecule Kartogenin from varying concentrations and ratios of cryogels was in between 32 and 66% through 21 days of incubation. Physical, mechanical, and chemical properties make LX and LXM polysaccharide-based cryogels promising candidates for cartilage and other soft tissue engineering, and drug delivery applications.
Keywords: Tissue Engineering; Tissue Scaffolds; Cell Survival; Mastic Resin; Polysaccharides, Bacterial; Phthalic Acids; Mesenchymal Stem Cells; Galactans; Rats; Mannans; Rats, Sprague-Dawley; Drug Liberation; Mice; Delayed-Action Preparations; Plant Gums; NIH 3T3 Cells; Animals; Anilides; Porosity; Cryogels